The Role of Morals in Ancient Society - Kalenda, Česlovas (Problemos, 1972)
The article deals with the problem of contradiction between the due and the real in the morals of the ancient slave-holding society. In spite of the f act that some Greek philosophers (Socrates, Plato, Aristotle and others centered their attention upon the problem of education, persistently trying to bring up their fellow citizens in the spirit of solidarity, mutual aid, friendship, brotherhood and so on, their noble ideas, however, were far from being realized. The author finds the slave-holding economic system to be the reason for the above failure.